Environmental issues: managing product switching intentions among Indonesian consumers. Issue 1 (2nd January 2018) - Burhanudin, Burhanudin; Ferguson, David
Abstract : Purpose: This study aims to explore the factors that make Indonesian consumers differ in their intentions to switch to products that are more eco-friendly than their current products. Design/methodology/approach: Consumers' experiences with their current product and evaluation of its more eco-friendly alternative were simulated; the effects on intention to switch to the better product were then investigated. Findings: This study found that the differences in intentions to switch are attributable to loss aversion and focusing illusion. When consumers follow the principle of loss aversion (exaggeration of greater loss than gain), they are more likely to switch to leave unattractive product (i.e. a product that they perceive as contributing to environmental degradation) than when they do not. Also, when consumers experience focusing illusion concerning the environment (determining happiness based on environmental conditions), they are more likely to switch to make their lives happier than when they do not. Practical implications: In managing consumer intention to switch, companies should effectively communicate how their products save the environment. This communication could make their customers less likely to give up their current products to live happier lives. Similarly, companies could encourage target customers to switch to their products by arguing that giving up their current products would help them live happier lives. Originality/value: This study provides empirical evidence that perceived budget constraints may not inhibit consumers from switching to more eco-friendly products to live happier lives.